2020
DOI: 10.3390/biology9120443
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-Binding Cassette (ABC) Transport Systems in Mycobacterium tuberculosis: Structure, Function, and Possible Targets for Therapeutics

Abstract: Mycobacterium tuberculosis is the etiological agent of tuberculosis (TB), a disease that affects millions of people in the world and that is associated with several human diseases. The bacillus is highly adapted to infect and survive inside the host, mainly because of its cellular envelope plasticity, which can be modulated to adapt to an unfriendly host environment; to manipulate the host immune response; and to resist therapeutic treatment, increasing in this way the drug resistance of TB. The superfamily of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 133 publications
(245 reference statements)
1
26
0
Order By: Relevance
“…The relevance of the characterization of the peptide transporter system has been described by Dasgupta et al (2010) . Previous studies uncovered the novel observation that this peptide transporter modulates the innate immune response of macrophages infected ( Cassio Barreto de Oliveira and Balan, 2020 ) with Mtb, but the epistatic interactions of oppA with other loci remain unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of the characterization of the peptide transporter system has been described by Dasgupta et al (2010) . Previous studies uncovered the novel observation that this peptide transporter modulates the innate immune response of macrophages infected ( Cassio Barreto de Oliveira and Balan, 2020 ) with Mtb, but the epistatic interactions of oppA with other loci remain unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has also been demonstrated that this transporter is implicated in the maintenance of chronic infection in murine models by mediating the transport of a molecule that can directly or indirectly modulate the proinflammatory host response. Despite having different structures, BacA and OppA shared their ability to transport a wide range of substrates; in particular, the shared capacity of import peptides related to the innate immune response suggests a complex regulation and interaction of these transporters, guaranteeing the need to carry out studies at the level of gene regulation and function in the near future ( Domenech et al, 2009 ; Cassio Barreto de Oliveira and Balan, 2020 ; Rempel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of this methyltransferase I resulted in the increased susceptibility of Melissococcus plutonius to mirosamicin antibiotics (Takamatsu et al, 2018 ). On the other hand, the ABC transporter substrate binding protein (Spots T388, T490, and T549) was produced by V. cholerae N4-21 when grown in P. viridis matrix, which participated in cell detoxification, antibiotic, and drug efflux in M. tuberculosis and greatly affected the survival and development of many drug-resistant strains (Cassio Barreto De Oliveira and Balan, 2020 ). Moreover, the TolC family outer membrane protein (Spots T446), produced by V. cholerae N4-21 in P. viridis matrix, was present in many pathogenic Gram-negative bacteria, including V. cholerae, E. coli , and P. aeruginosa , and formed an outer membrane channel that removed drugs and toxins from cells (Leong et al, 2014 ; Pattanayak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The process includes the binding of nuclear binding domains (NBDs) of ABC transporters with the Adenine triphosphate (ATP) and followed by ATP hydrolysis for energy production required for this process to be carried out. NBD is the most conserved domain of the transporters, having all about 40-45% conserved sequences, irrespective of their substrate specificity and their origin [12,13]. Approximately all NBD-containing proteins are responsible for the transportation of substrate across the plasma membranes.…”
Section: Introductionmentioning
confidence: 99%